POTENSI SENYAWA BIOAKTIF TANAMAN GENUS Phyllanthus SEBAGAI INHIBITOR REPLIKASI VIRUS HEPATITIS B - Firdayani, .; Kusumaningrum, Susi; Miranti, Yosephine Ria (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2017)
Potency of Plant Bioactive Compounds from the Genus Phyllanthus as Hepatitis B Virus Replication InhibitorIn this research, simulations of molecular docking of Phyllanthus bioactive compounds were performed into the core protein of HBV. This simulation aimed to predict the interaction between compounds with virus core protein causing disruption of capsid formation and inhibiting its replication. The docking simulation was completed by Molegro Virtual Docker 6.0. The 3D stable conformation of molecule structures were docked into HBV core protein downloaded from Protein Data Bank, then the results were analyzed to view the minimum energy and interactions that occurred. The coordinate docking was done at the same coordinate as the previously docked reference ligand position and was validated. From the results it was known that repandusinic acid formed the most stable affinity bond with amino acid residues of viral core proteins. Interaction of B chain forming hydrogen bonds with the amino acid residues of Thr 33, Trp 102, Phe 23, Leu 140, Tyr 118 and Ser 141, and C chain with Thr 128, Val 124 and Glu 117.These compounds can be used as marker for anti HBV.Keyword: Bioactive compounds, core protein, HBV , molecular docking, Phyllanthus ABSTRAKPada penelitian ini dilakukan simulasi penambatan molekul senyawa-senyawa bioaktif Phyllanthus ke dalam protein inti virus hepatitis B. Simulasi ini bertujuan untuk memprediksi interaksi terbentuk antara senyawa dengan protein yang menyebabkan terganggunya pembentukan kapsid virus dan menghambat replikasinya. Simulasi penambatan molekul dilakukan menggunakan program Molegro Virtual Docker 6.0. Sebagai reseptor target digunakan struktur 3D protein inti yang diunduh dari Protein Data Bank. Posisi penambatan dilakukan pada koordinat yang sama dengan posisi ligan referensi yang sudah tertambat sebelumnya dan tervalidasi. Dari hasil simulasi diketahui bahwa asam repandusinat membentuk komplek dengan energi afinitas ikatan yang paling kecil dengan residu asam amino protein inti virus. Interaksi terjadi dengan rantai B yang membentuk ikatan hidrogen dengan asam amino Thr 33, Trp 102, Phe 23, Leu 140, Tyr 118 dan Ser 141, dan rantai C dengan asam amino Thr 128, Val 124 dan Glu 117. Senyawa ini dapat dijadikan sebagai marka untuk anti VHB.Kata kunci: Penambatan molekul, Phyllanthus, protein inti, senyawa bioaktif, VHBReceived: 11 December 2017                 Accepted: 27 December 2017           Published: 31 December 2017